Implementasi Terapi Kelompok Teraupetik dan Peer Leadership Guna Menurunkan Prodroma dan Ide Bunuh Diri Remaja - Silalahi, Malianti; Casman,; Fitria, Dian; Setyaningsih, Tri; Rahmawati, Veronica; Atshillah, Zakiyyah; Salsabila, Adinda (Idea Pengabdian Masyarakat, 2022)
Suicide is a one of adolescents mental health problem in Indonesia. Some adolescents with psychological problems show symtomp such as suicidal ideation, have planned suicide and progress to suicidal attempt if the problem unsolved. One of preventive activity is provide education about early signs and symptoms of early psychosis (prodroma early psychosis). Based on the survey done by team showed that there was fourty adolencents in one of Pasar Baru villages had not been exposed to education related to suicide in adolescents. This is a priority problem to solved, so that it is important to give counseling and education to adolescent. Nursing Intervention therapy involed to two activity such as Therapeutic Group Therapy is the one of therapy consist of knowledge about adolescent growth and development task. Next intervention is giving education dan counceling about the description of the prodroma of early psychosis, and followed peer leadership as an effort to prevent suicide in adolescents. Therapeutic Group Therapy and Peer Leadership as nursing therapy to prevent suicide in adolescents which is applied to the one of area in Pasar Baru urban Village. The method is through counseling and discussions followed by therapeutic group therapy and peer leadership to adolescents. The result has been shown through these two therapy can reduce prodroma early psychosis 64.3% in adolescents and decrease in suicidal ideation to 14.3% post therapy.